Effects of hydrodynamic regimes from a proposed marine park in monsoon seasons - N.T. Mai; N.T.M. Hang (International Association of Lowland Technology, 2018)
The process of building the Son Tra Ocean Park in Danang city, Vietnam will contribute certain impacts to hydrodynamic regimes leading to erosion or accretion on the coast. In this paper, we used numerical models to simulate hydrodynamic flows, waves, and sediment transport for two scenarios of “without” and “with” project. The results showed that the Park would alter the dynamic flow and lithospheric process in the area and surrounding. Most affected range is of about 200m-800m from the location adjacent of Park. Nearshore current velocity is increased and accretion and erosion in monsoon seasons are usually mild.